P68 Relationship between socioeconomic status and gastrointestinal infections in developed countries: a systematic review and meta-analysis. (2nd September 2017) - Adams, NL; Rose, TC; Hawker, J; Violato, M; O'Brien, SJ; Barr, B; Howard, VJK; Whitehead, M; Harris, R; Taylor-Robinson, DC
Abstract : Background: The public health impact of gastrointestinal (GI) infections is substantial, with around a quarter of individuals experiencing an episode of infectious gastroenteritis each year. Yet relatively little is known about the social patterning of these infections. Studies investigating the association between socioeconomic status (SES) and risk of GI infections have produced conflicting results, with some reporting greater risk amongst lower SES and other observing the opposite effect. This systematic review and meta-analysis aimed to assess the association between SES and risk of GI infections, and explore possible sources of heterogeneity in effect estimates reported in the literature. Methods: MEDLINE, Scopus, Web of Science and grey literature were searched from 1980 to October 2015 for studies reporting a quantitative association between GI infections and SES in a representative population sample from a member-country of the Organisation for Economic Co-operation and Development. Quality assessment was conducted using the Liverpool University Quality Assessment Tool. Harvest plots were created for comparison where heterogeneity between studies was high, stratified by age, SES measurement, GI infection measurement and pathogen type. Meta-analysis was conducted on a subset of data. To explore sources of heterogeneity, meta-regression and stratified meta-analyses were performed on the basis of country, age, pathogen type, GI infection measurement and SES measurement. The protocol was registered on PROSPERO: CRD42015027231. Results: In total, 6021 studies were identified; 102 met the inclusion criteria. Overall risk of GI infection for low versus high SES was 1·06 (95%CI 0·95–1·19). For children, risk was higher for those of low SES versus high (RR 1·51, 95% CI 1·26–1·83), but there was no association for adults (RR 0·83, 95% CI 0·61–1·14). Results were similar when sensitivity analyses were performed on the basis of study quality. Age explained a small proportion of the overall heterogeneity. Discussion: We quantify, for the first time, the association between SES and risk of GI infection in developed countries and show that disadvantaged children, but not adults, appear to be at greater risk of GI infection compared to their more advantaged counterparts. Increased risk may relate to differential exposures, vulnerability or healthcare-seeking behaviours by SES. It is possible that factors that could not be adjusted for may explain the high residual heterogeneity. Strategies to improve childhood socioeconomic conditions are likely to reduce the burden of GI illness. Gaining greater insight into this relationship will help to inform policies to reduce the health inequalities identified.